PP.39.26: ANGIOTENSIN CONVERTING ENZIME POLYMORPHISMS ARE ASSOCIATED WITH POST-EXERCISE HYPOTENSION IN HYPERTENSIVE PATIENTS. (June 2015) - Goessler, K.; Cornelissen, V.; De Oliveira, E.M.; Mota, G.F.; Polito, M.
Abstract : Objective: The adoption of a healthy lifestyle is an essential component in blood pressure (BP) management. Both acute and chronic exercises have been shown to lower BP, especially in hypertensive individuals. However, not all individuals respond similarly to exercise. Limited data suggest that polymorphisms of the angiotensin converting enzyme (ACE)-gene can interfere with the exercise induced acute BP reductions. The aim of this pilot study was to evaluate the effect of the ACE polymorphism (insertion / deletion) on post-exercise hypotension in medicated hypertensive patients. Design and method: Baseline measurements of office BP were performed after 15 minutes of seated rest in 43 hypertensive patients (14 men; mean age 69.9 ± 9.3 yrs). Then, all participants performed one walking session of 45 minutes at 60–75% of heart rate reserve. Following this exercise session, office BP was measured every 10 minutes for one hour by means of an oscillometric automatic device. ACE genotyping was performed by means of polymerase chain reaction; and the ACE gene was classified into three types: I/I, I/D and D/D. Carriers of the I allele (II and ID) were compared to individuals with ACE D/D polymorphism. Results: At baseline, systolic BP (p = 0.21) and diastolic BP (p = 0.94) were similar for both groups and averaged 133.4 ± 16.1 / 84.3 ± 9.0 mmHg. Both groups showed a significant reduction in systolic BP following the walking session (p < 0.01). However, the reduction in systolic BP was significantly larger at all-time points for individuals with an I allele compared to the individuals homozygous for the D allele (Figure 1A). There were no significant changes in diastolic BP following exercise (p = 0.75) (Figure 1B). Figure. No caption available. Conclusions: The present study suggests that the ACE-gene is associated with acute BP reductions following exercise. Larger randomized controlled trials are warranted to confirm our findings.